Ruscogenin Attenuates Lipopolysaccharide-Induced Septic Vascular Endothelial Dysfunction by Modulating the miR-146a-5p/NRP2/SSH1 Axis - Pan D; Zhu J; Cao L; Zhu B; Lin L (Dove Medical Press, 2022)
Danhong Pan,1 Jinqiang Zhu,2 Liexiang Cao,2 Beilei Zhu,3 Lili Lin1 1Emergency Care Unit, The First People's Hospital of Wenling, Wenling, Zhejiang, 317500, People's Republic of China; 2Emergency Department, The First People's Hospital of Wenling, Wenling, Zhejiang, 317500, People's Republic of China; 3Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People's Republic of ChinaCorrespondence: Lili Lin, Emergency Care Unit, The First People's Hospital of Wenling, No. 333, Chuan'an South Road, Chengxi Street, Wenling, Zhejiang, 317500, People's Republic of China, Tel +86- 13616760809, Email lllin_24126_zh@hotmail.comIntroduction: Endothelial dysfunction (ED) is associated with the progression of sepsis. Ruscogenin (RUS) has shown considerable efficacy in treating ED and sepsis. In the current study, the effects of RUS on sepsis-induced ED were assessed, and the mechanism was explored by focusing on the interactions of RUS with miRs.Methods: Sepsis was induced in mice and in human umbilical vein endothelial cells (HUVECs) using LPS method. Expression profile of miRs responding to sepsis was determined. Symptoms associated with sepsis and ED were examined after treatment with RUS. Changes in mouse survival, arterial structure, systemic inflammation, cell viability, apoptosis, and the miR-146a-5p/NRP2/SSH1 axis were analyzed.Results: Based on the microarray results, miR-146a-5p was selected as the therapeutic target. RUS improved survival rates and arterial structure, suppressed proinflammatory cytokines, down-regulated miR-146a-5p, and up-regulated NPR2 and SSH1 in septic mice. In HUVECs, RUS increased cell viability, suppressed apoptosis, inhibited inflammation, downregulated miR-146a-5p, and increased NRP2 and SSH1 levels. The re-induction of miR-146a-5p-5p impaired the protective effects of RUS on HUVECs.Discussion: Effects of RUS on sepsis-induced impairments in endothelium relied on the suppression of miR-146a-5p.Keywords: endothelial dysfunction, ruscogenin, miR-146a-5p, NRP2, sepsis